Hybrid Assembly of Complete Genomes of Yersinia pestis Strains - A. V. Fedorov; Ya. M. Krasnov; E. A. Naryshkina; E. A. Sosedova; A. D. Katyshev; G. A. Eroshenko; L. M. Kukleva; N. A. Osina; V. V. Kutyrev (Проблемы особо опасных инфекций, 2024)
The aim of the study was to assemble full-length nucleotide sequences of the chromosome and plasmids for 13 Yersinia pestis strains from 11 natural plague foci located in the Russian Federation, using data from two sequencing technologies.Materials and methods. Y. pestis strains were grown on Hottinger’s agar (pH 7.2) at 37 °C. DNA was isolated using phenol-chloroform extraction. For the MinIon genetic analyzer (Oxford Nanopore), DNA fragments were prepared by ligation according to a modified protocol. For the Ion S5 genetic analyzer (IonTorrent), sample preparation was carried out according to the standard protocol for obtaining a library with a DNA fragment size of 400 nucleotide pairs (bp). The resulting single reads were filtered by average quality Q30 for IonTorrent and Q7 for Oxford Nanopore.Results and discussion. DNA fragments containing 50 000 or more nucleotide pairs were prepared for subsequent sequencing using nanopore sequencing technology (Oxford Nanopore). The Trycycler algorithm was applied for hybrid assembly of the genome of Y. pestis strains and correction of errors arising during this process, allowing the obtainment of full-length nucleotide sequences of the chromosome and plasmids for each genome of the strain. The nucleotide sequences of the chromosomes of 13 Y. pestis strains from 11 natural foci of plague located in the Russian Federation have been deposited in the international genetic database NCBI GenBank. It has been established that to assemble full-length genomes of Y. pestis strains, a significant number of reads with a size of 50 000 bp or more is required, and the use of the Trycycler algorithm allows one to generate a more accurate assembly of complete bacterial genomes.